Penerapan Model Problem Based Learning (PBL) dalam Pembelajaran Bahasa Indonesia Materi Surat Resmi di SMPN 1 Banjarmasin - Nadina, Diya Amalia (UPA Bahasa Universitas Tidar And HISKI Kedu, 2025)
This study aims to describe the implementation of the Problem Based Learning (PBL) model in Indonesian language learning on the topic of official letters and to examine its impact on students’ writing skills in Grade VII at SMPN 1 Banjarmasin. The research employed Classroom Action Research (CAR) with a qualitative descriptive approach involving 31 students as participants. The findings indicate that the application of PBL increased student engagement through group discussions, independent investigations, and project presentations. Most students successfully composed official letters using proper structure and formal language, as reflected in the majority achieving scores in the good category. PBL also fostered students’ critical thinking, collaboration, and responsibility throughout the learning process. Therefore, PBL is proven to be an effective model for improving students’ understanding and writing skills related to official letters.